Test–Retest Reliability of Mismatch Negativity (MMN) to Emotional Voices - Chen, Chenyi; Chan, Chia-Wen; Cheng, Yawei (Frontiers in Human Neuroscience, 2018)
Voice from kin species conveys indispensable social and affective signals with uniquely phylogenetic and ontogenetic standpoints. Among all, the neural underpinning of emotional voices, beyond low-level acoustic features, activates a processing chain that proceeds from the auditory pathway to the brain structures implicated in cognition and emotion. Using a passive auditory oddball paradigm deployed with emotional voices, this study investigates the test-retest reliability of emotional mismatch negativity (MMN), indicating that the deviants of positively (happily)- and negatively (angrily)-spoken syllables, as compared with neutral standards, can trigger MMN in response to automatic discrimination of emotional salience. The neurophysiological estimates of MMN to positive and negative deviants appear highly reproducible irrespective of whether subjects pay attention to watch a silent movie or do a working memory task. Specifically, negativity bias is evinced, where threatening relative to positive vocalizations consistently induce larger MMN amplitudes on different days and at different times of day. The present findings provide evidence to support that emotional MMN offers a stable platform to detect subtle changes in current emotional shifts. We should take into accounts the online emotional state at individual level when applying MMN as a diagnostic biomarker for translational medicine.